(untitled) (International Conference on Education, Psychology and Humanities, 2026)
This article explores the didactic potential and effectiveness of the microteaching method in enhancing quality instruction within the continuous teacher education system for the subject of Moral Education. It theoretically substantiates the issues of developing pre-service teachers’ analytical competence, fostering reflective practice mechanisms, and designing variable educational processes. Through a comparative analysis of international and national pedagogical experiences, methodological recommendations are developed to systematically integrate the microteaching method into the curricula of higher pedagogical education.